2009
DOI: 10.1179/106698109790818197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perspective: How Do Clinical Test Results Differentiate Chronic and Subacute Low Back Pain Patients from "Non-Patients"?

Abstract: Our limited understanding of underlying conditions for back pain is reflected in the common use of pain-duration-based groupings. The aim of this paper was to investigate typical clinical tests used in examining low back pain (LBP) patients in order to discover how tests distinguish between chronic low back pain patients (CLBP) and subacute low back pain patients (SLBP) and if they distinguish these groups from those with no "patient status." CLBP patients in this study were from a university hospital and SLBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…We previously demonstrated the sensitivity and specificity of the clinical tests used to distinguish clinically relevant subgroups in the early phase of LBP management. 17,18 Based on these studies, the intraand inter-reliability of the clinical tests used for this study and the clinical test clusters to determine the classification level is good for different testers. 24 The patients' symptoms and onset of the pain mechanism served as the basis for clinical reasoning in the diagnostic decision-making process (Appendix).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously demonstrated the sensitivity and specificity of the clinical tests used to distinguish clinically relevant subgroups in the early phase of LBP management. 17,18 Based on these studies, the intraand inter-reliability of the clinical tests used for this study and the clinical test clusters to determine the classification level is good for different testers. 24 The patients' symptoms and onset of the pain mechanism served as the basis for clinical reasoning in the diagnostic decision-making process (Appendix).…”
Section: Methodsmentioning
confidence: 92%
“…13 Subsequent studies have further refined the existing guidelines for classifying patients with NSLBP using more detailed examination criteria. [14][15][16][17][18] However, to date, there is no consensus on which of the LBP classification systems is more accurate or appropriate in the early phase of LBP, and praxis varies. 9,19 Nevertheless, the question arises as to whether or not PTs can learn to apply a specific classification system for patients with non-specific LPB within the context of a continuing education course.…”
Section: Introductionmentioning
confidence: 99%
“…Although pain duration and location and neurologic status classes may be useful patient descriptors, pain duration was unable to predict subjects' response to treatment [17,52]. Paatelma et al [67] investigated the ability of clinical tests to distinguish between subacute and chronic LBP and concluded that “subgrouping based on pain duration, as presently recommended by current clinical practice guidelines, may not be an optimal or diagnostically accurate understanding of subjects with chronic or subacute LBP problems.”…”
Section: Discussionmentioning
confidence: 99%
“…With specific pain loading/provocation or pain relieving tests it may be possible to determine from which tissue/structure the nociceptive stimulus is primarily coming. (27,28,(32)(33)(34). Although positive and negative findings of clinical tests do not explain why these tissues/structures are overloaded or strained, they are important when explaining the pain mechanism to patients and when pain treatment for the early phase is designed.…”
Section: Clinical Tests Of Low Back Pain In Early Phasementioning
confidence: 99%